Characteristics of stratified flows of Newtonian/non-Newtonian shear-thinning fluids. (December 2017) - Picchi, Davide; Poesio, Pietro; Ullmann, Amos; Brauner, Neima
Highlights: Exact solution for laminar stratified flow of Newtonian/Carreau fluid is obtained. The effect of the rheology on two-phase flow characteristics is studied. Two-phase stratified flow can behave like the liquid is Newtonian. Boundaries of multiple solution regions are identified and mapped. Two-Fluid model closures are discussed for this case. Abstract: Exact solutions for laminar stratified flows of Newtonian/non-Newtonian shear-thinning fluids in horizontal and inclined channels are presented. An iterative algorithm is proposed to compute the laminar solution for the general case of a Carreau non-Newtonian fluid. The exact solution is used to study the effect of the rheology of the shear-thinning liquid on two-phase flow characteristics considering both gas/liquid and liquid/liquid systems. Concurrent and counter-current inclined systems are investigated, including the mapping of multiple solution boundaries. Aspects relevant to practical applications are discussed, such as the insitu hold-up, or lubrication effects achieved by adding a less viscous phase. A characteristic of this family of systems is that, even if the liquid has a complex rheology (Carreau fluid), the two-phase stratified flow can behave like the liquid is Newtonian for a wide range of operational conditions. The capability of the two-fluid model to yield satisfactory predictions in the presence of shear-thinning liquids is tested, and an algorithm is proposed to a priori predict if the Newtonian (zero shear rate viscosity) behaviour arises for a given operational conditions in order to avoid large errors in the predictions of flow characteristics when the power-law is considered for modelling the shear-thinning behaviour. Two-fluid model closures implied by the exact solution and the effect of a turbulent gas layer are also addressed.